How Islam Addresses Poverty and Income Inequality - Meti Astuti (Yayasan Rumah Peneleh, 2022)
For decades, poverty and income inequality have always been the scourge of skyrocketing economic growth and remarkable development. This paper attempts to explain the main causes of poverty and income inequality which arethe poor distribution of wealth and lack of opportunity for individual people to acquire wealth and use it. The main cause is the granting of free access to individuals and the private sector to take advantage of economic resources with the power of connection and the granting of privileges through laws and regulations in favor of private foreign funds. In the Islamic economic system, the right to ownership of economic resources provides space for individuals to participate in the development and have access to resources, which is currently dominated by the private sector. The method used in this paper is descriptive qualitative, by exploring literatures of thought of Muslim scholars. The pillars of Islamic economics that regulate ownership of property and the rules on how to use and develop it as well as provide guide distribution of wealth amidst society have brought Islamic society to the era of the glory of Islam where there is justice in economic development.